Maternal diet alters long-term innate immune cell memory in fetal and juvenile hematopoietic stem and progenitor cells in nonhuman primate offspring - Michael J. Nash; Evgenia Dobrinskikh; Taylor K. Soderborg; Rachel C. Janssen; Diana L. Takahashi; Tyler A. Dean; Oleg Varlamov; Jon D. Hennebold; Maureen Gannon; Kjersti M. Aagaard; Carrie E. McCurdy; Paul Kievit; et al. (Cell Reports, 2023)
Summary: Maternal overnutrition increases inflammatory and metabolic disease risk in postnatal offspring. This constitutes a major public health concern due to increasing prevalence of these diseases, yet mechanisms remain unclear. Here, using nonhuman primate models, we show that maternal Western-style diet (mWSD) exposure is associated with persistent pro-inflammatory phenotypes at the transcriptional, metabolic, and functional levels in bone marrow-derived macrophages (BMDMs) from 3-year-old juvenile offspring and in hematopoietic stem and progenitor cells (HSPCs) from fetal and juvenile bone marrow and fetal liver. mWSD exposure is also associated with increased oleic acid in fetal and juvenile bone marrow and fetal liver. Assay for transposase-accessible chromatin with sequencing (ATAC-seq) profiling of HSPCs and BMDMs from mWSD-exposed juveniles supports a model in which HSPCs transmit pro-inflammatory memory to myeloid cells beginning in utero. These findings show that maternal diet alters long-term immune cell developmental programming in HSPCs with proposed consequences for chronic diseases featuring altered immune/inflammatory activation across the lifespan.